MODEL PEMBELAJARAN SEKOLAH HIJAU DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Muhammad Zaini (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2010)
Abstract. Implementation of green school instructional model to improve the quality of science teaching and learning at elementary school at South Kalimantan Province was observed. Research subjects ware devided to three groups, namely elementary school at waters area, transition of peat and mountain range area and mountain area. Research data collected concise of learning outcome and learning activity. Then, they were analyzed by using anava and descriptive approach respectively. This research reveals that (1) learning activity of student both at waters area and transition of peat and mountain range area were high, meanwhile at mountain range area and mountain is relatively low (2) teacher role both at waters area and transition of peat and mountain range area were still dominant, meanwhile at mountain range area and mountain is unsufficient (3) threre is significant difference of learning outcome between all the areas (4) and the student reached it at a good level.Key words: science, green school, learning activity, learning outcome